Dynamic optimization of the mashing process - Durand, Guillermo Andrés (2009)
This work aims to demonstrate the applicability of dynamic optimization to improve the time-temperature schedule of a brewery mashing process, based on kinetic models available in the literature. The mashing process consists in the enzymatic degradation of the polysaccharides present in the malt. This is a fundamental step within the brewery activity since the composition of the mashing wort determines the quality of the final product. The main reactions that take place in the mashing are the degradation of starch, β-glucans and arabinoxylans into small chain fermentable and non-fermentable carbohydrates. The manipulation of the temperature profile of the batch reactor is the main mechanism to control the extent of the ongoing reactions. Since high temperatures favor the production of fermentable matter but also increases the concentration of undesirable species in the wort, the choice of an adequate temperature profile is not obvious. Dynamic optimization studies with a complete mashing model demonstrate that profiles of "temperature averages" of about 51 °C are preferred over typical industrial mashings of 64 °C to optimize the operation. © 2009 Elsevier Ltd. All rights reserved.